Programma: 6-9 november John Bull; Mary Fulkerson; 13-16 november Tie 3; Athenea Baker; 20-23 november Natural Theatre, Sonny Hayes; 27-30 november Chiclayo, Piro (1976)
Programma: 6-9 november John Bull; Mary Fulkerson; 13-16 november Tie 3; Athenea Baker; 20-23 november Natural Theatre, Sonny Hayes; 27-30 november Chiclayo, Piro.